In situ studies of the adsorption kinetics of 4-nitrobenzenediazonium salt on gold - COLAVITA, PAULA (My University, 2011)
Self-assembled organic layers are an important tool for modifying surfaces in a range of applications in materials science. Covalent modification of metal surfaces with aryldiazonium cations has attracted much attention primarily because this reaction offers a route for spontaneously grafting a variety of aromatic moieties from solution with high yield. We have investigated the kinetics of this process by performing real-time, in situ nanogravimetric measurements. The spontaneous grafting of 4-nitrobenzene diazonium salts onto gold electrodes was studied via quartz crystal microbalance (QCM) from aqueous solutions of the salt at varying concentrations. The concentration dependence of the grafting rate within the first 10 min is best modelled by assuming a reversible adsorption process with free energy comparable to that reported for arylthiols self-assembled on gold. Multilayer formation was observed after extended grafting times and was found to be favoured by increasing bulk concentrations of the diazonium salt. Modified gold surfaces were characterized ex situ with cyclic voltammetry, Infrared Reflection Absorbance Spectroscopy and X-ray Photoemission Spectroscopy. Based on the experimentally determined free energy of adsorption and on the observed grafting rates we discuss a proposed mechanism for aryldiazonium chemisorption.
PUBLISHED
Keywords: functionalization; diazonium; aryldiazonium; gold; QCM; Langmuir; adsorption; chemisorption; Nanoscience & Materials